Effect of abiotic factors on Marssonina blotch causing premature leaf fall in apple (Malus domestica) - and J.N. SHARMA, ANIL KUMAR* (Indian Phytopathology, 2013)
The effect of abiotic factors viz., temperature, relative humidity and duration of leaf wetness period on in vitro conidial production, germination and infection in detached apple leaves by Marssonina coronaria causing Marssonina blotch, was studied. Conidia germinated over a wide range of temperature tested (5-30Â°C), the optimum temperature for germination was 20Â°C. Conidia also wide germinated well under all relative humidity levels tested (40-100%), however, best germination was recorded at near saturation humidity (> 90%). In the present investigation, combination of temperature 200C and leaf wetness of 48h was recorded the most favourable for development of Marssonina blotch of apple and a minimum 6 h of leaf wetness was required by the test pathogen to cause infection in apple leaves. A field experiment was also conducted during 2009 and 2010 to investigate the influence of meteorological parameters on Marssonina blotch development under field conditions. The correlation analysis showed that among all the meteorological factors considered relative humidity was the key factor to govern the disease in the field. Severity of Marssonina blotch showed significantly correlated with relative humidity. Multiple regression equation was developed with coefficient of multiple determination (R2) of 0.9161 and 0.9703 in year 2009 and 2010, respectively.